Indiscipline Related Behaviour and Academic Performance of Secondary School Students in Mathematics in Calabar Education Zone of Cross River State, Nigeria - Bassey, Edwin Okpa; Otu, Bernard Diwa (NIU Journal of Social Sciences, 2025)
The purpose of this study was to examine the relationship between indiscipline related behaviours and academic performance of secondary school students in mathematics in Calabar Education Zone of Cross River State, Nigeria. To achieve the purpose of this study three null hypotheses were generated to direct the study. Literature review was done according to the variables under study. Correlational research design was adopted for the study. This design was considered appropriate because it allowed the researcher to measure the relative and composite contributions of tendency to indiscipline related behaviour and secondary school students’ academic performance. A sample of three hundred and thirty-six (336) respondents was randomly selected for the study. The selection was done through the stratified random sampling technique. The  questionnaire was the main instrument used for data collection. The instrument was subjected to face validation by experts in measurement and evaluation in the Faculty of Education, University of Calabar. The reliability estimate of the instrument was established through the Cronbach alpha reliability method. Regression analysis was the statistical analysis technique adopted to test the hypotheses under study. The results of the analysis revealed that, bullying, absenteeism, truancy, lateness to school and examination dishonesty significantly relate to students’ academic performance in mathematics. Based on the findings of the study it was recommended among others that principals and teachers should check mate bullying by disciplining any student who intentionally or incidentally engages in these dastardly acts, that students should be made to understand the dangers of examination malpractice and culprits caught in examination should be used to set good examples for others to enable them model adequate behaviours and study hard for their examination.